Enhance Mathematical Understanding By Discovery Learning - Rita Syara; Ujang Cahya Setia; Rosalina Rolina (IKIP Siliwangi, 2018)
This research is motivated by the low ability of understanding vocational students. This study will examine the improvement of students' mathematical understanding ability using discovery learning with the usual approach. The method used is the experimental method with the design of pretest-posttest control groups, namely designs that involve at least two groups and random sampling of classes. At the beginning and end of the study both classes are given a test. The population in this sample are all vocational high school students whose characteristics have low mathematical comprehension ability. Of all vocational schools randomly selected and selected Cimahi IT Development Vocational Schools representing the characteristics of the population. The sample was chosen randomly, where class XI RPL C became the experimental class, and class XI TEI B became the control class. Collecting data in this study using a description test that has been tested beforehand, then the scores of students' mathematical comprehension ability were analyzed with descriptive and inferential statistics using two average difference tests. Based on the results of the study, both data analysis and hypothesis testing, with α = 0.05, it was found that the improvement of students' mathematical understanding ability using discovery learning was better than students who used the usual approach, as well as the achievement of better understanding abilities. Keywords: understanding, discovery learning.